PENGARUH PENGELUARAN PEMERINTAH DI BIDANG PENDIDIKAN DAN KESEHATAN TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) DI KABUPATEN/KOTA PROVINSI KALIMANTAN BARAT - B01109021, HENDY DEVITSEN (Jurnal Pembangunan dan Pemerataan, 2015)
Research about The effect of goverment spanding in education and health of the  Human Development Index (HDI) in the district/city in west Kalimantan Province. This study aims to determine the effect of these variabel on local goverment spanding on education and health to the Human Development Index (HDI) in particular time priod 2008-2012. The methodology used  in this resech descriptive research data used are secondary. The type of data used are secendary data publised by by the Directorate General Of Regional Finance and the Central Berau of Statistic (BPS) the other agencius, Then the data is processed using Eviews 6 program with panel data regression analysis, fixed effect model approach. Regression results using fixed effect models showed that the goverment spanding for education and health simultaneouly have a positive and significant impact on the increase in the Human Development Index in the district/city of west Kalimantan Provence. HDI figures, the increase in the priode 2008 to 2012. This means that the larger of goverment spanding for education and health, the greater the effect on HDI west Kalimantan. While the partially show the goverment spanding for education has positive and significant effect on the increase in the Human Development Index (HDI) in the district/city of west Kalimantan Province, seen the average length in the district/city of west Kalimantan Province value continues the incrase. While the goverment spanding for health sector is positive but not significant  effect on the Human Development Index in the district/city of west Kalimantan Provence. This is due to the high infant and maternal mortality rates and life expectansy is still low in the district/city of west Kalimantan Provence. In addition to adequate healt care fasilities, and other supporting  also needed to fasilitate the public to reach out to access existing health and public awareness of health also needs to be improved. Keywords : HDI, Goverment Expenditure for education, Goverment Spending Health, Panel Data Regression.